Consecration of the legal status of treaties by the control of the Constitutional Court (Numerus academy review, 2026)
The preamble to the Algerian constitution enshrined the principle of theconstitution supremacy, and the constitutional amendment created a constitutional courtwith jurisdiction over constitutional oversight, in addition to other constitutional competencies that would protect the state’s legal system. This amendment strengthenedthe jurisdiction of this court to control the constitutionality of treaties, by controlling thecompatibility of laws and regulations with treaties, which is devoted to the protection ofthe supremacy of the Constitution over international rules, and the superiority of treatiesover domestic laws. But, to achieve this purpose, the ambiguity must be lifted over theconstitutional texts related to the field of these two controls and the implications for them,as a guarantee for activating the role of the Constitutional Court in establishing the rankof treaties within the hierarchy of legal rules.